Preparation and characterization of jackfruit seed starch/poly (vinyl alcohol) (PVA) blend film - Sarifuddin, Norshahida; Shahrim, N.A.; Rani, N. N.S.A.; Zaki, H. H.M.; Ahmad Azhar, Ahmad Zahirani (Institute of Physics Publishing, 2018)
From the environmental point of view, biodegradable materials have been rapidly developed in the past years. PVA is one of the biodegradable synthetic polymers commonly used, but its degradation rate is slow. As an alternative to reduce plastic waste and accelerate the degradation process, PVA frequently blended with other natural polymers to improve its biodegradability. The natural polymer such as starch has high potential in enhancing PVA biodegradability by blending both components. The usage of starch extracted from agriculture wastes such as jackfruit seed is quite promising. In this study, jackfruit seed starch (JFSS)/poly (vinyl alcohol) (PVA) blend films were prepared using the solution casting method. The effect of starch content on the mechanical (tensile strength and elongation to break %) and physical properties of the tested films were investigated. The optimum tensile strength was obtained at 10.45 MPa when 4 wt. % of starch added to the blend. But, decreasing trend of tensile strength was found upon increasing the amount of starch beyond 4 wt. % in starch/PVA blend films. Nevertheless, elongation at break decreases with the increase in starch content. The mechanical properties of the blend films are supported by the Field Emission Scanning Electron Microscopy (FESEM), in which the native JFSS granules are wetted by PVA continuous phase with good dispersion and less agglomeration. The incorporation of JFSS in PVA has also resulted in the appearance of hydrogen bond peak, which evidenced by Fourier Transform Infrared (FTIR). Additionally, the biodegradation rate of JFSS/PVA was evaluated through soil burial test